The Juridical Analysis of Criminal Acts on Negligence of Traffic Accidents That Cause Death - Fitri Ida Laela (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to explain the problem, which is the basis or consideration of the judge in considering the elements of the criminal act of negligence in traffic accidents that result in the loss of other people's lives. This study is a literature study with a normative juridical approach. The data collection technique used in this research is the documentation technique. At the same time, the analysis technique used in this research is descriptive. The findings in this study are that the judge's considerations in determining criminal sanctions against perpetrators of criminal acts of negligence in traffic accidents are divided into two, namely, juridical considerations and non-juridical considerations. A judge gives juridical considerations to a case based on statutory regulations, indictments, and demands from the public prosecutor. The judge's consideration is also based on the facts found in the trial examination based on the evidence submitted. At the same time, non-juridical considerations include the judge's consideration of the factors that will burden the crime and the factors that relieve the perpetrators of the crime. Tujuan penelitian ini adalah menjelaskan permasalahnnya yang menjadi dasar atau pertimbangan hakim dalam mempertimbangkan unsur-unsur tindak pidana kelalaian kecelakaan lalu lintas yang mengakibatkan hilangnya nyawa orang lain. Studi ini adalah penelitian pustaka dengan pendekatan yuridis normatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik dokumentasi. Sedangkan Teknik analisis yang digunakan dalam penelitian ini adalah Deskriptif. Temuan dalam penelitian ini adalah pertimbangan hakim dalam menentukan sanksi pidana terhadap pelaku tindak pidana kelalaian atau kealpaan dalam kecelakaan lalu lintas terbagi menjadi dua yakni, pertimbangan yuridis dan pertimbangan non yuridis. Pertimbnagan yuridis merupakan pertimbangan yang diberikan oleh hakim terhadap suatu perkara berdasarkan peraturan perundang-undangan, dakwaan dan tuntutan yang diberikan oleh penuntut umum. Pertimbangan hakim ini juga berdasarkan kepada fakta-fakta yang ditemukan dalam pemeriksaan persidangan berdasarkan barang bukti dan alat bukti yang diajukan. Sedangkan pertimbangan non yuridis yakni pertimbangan hakim dari faktor-faktor yang akan memberatkan pelaku tindak pidana dan juga faktor-faktor yang meringankan pelaku tindak pidana.